RESPON PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris L.) TERHADAP BERBAGAI DOSIS MOL BONGGOL PISANG - Rahmida Rahmida; Ellisa Rusiani; Putri Rahayu; Zainab Zainab; Mahdiannoor Mahdiannoor (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Almost all societies use beans. Beans are the usual food consumed by the people of Indonesia. The local microorganism (MOL) is a fermented solution based on various locally available resources. MOL solution contains micro and macro nutrients and also contains potential bacteria as organic material remodel, growth stimulant and as agent of plant pests and diseases. The purpose of this study was to determine the growth response and plant yield (Phaseolus vulgaris L.) to various doses of MOL banana cobs, and get the best dose. This research was conducted at BPTP South Kalimantan in Muara Rintis Village, Batang Alai Utara Subdistrict, Hulu Sungai Tengah Regency, from April to July 2017. This research uses single factor RAK with 4 levels ie m1 = 125 ml per plant, m2 = 250 ml per plant , m3 = 375 ml per plant, m4 = 500 ml per plant each treatment was repeated 6 times so that there were 24 experimental units. The results showed no effect on the observed variables.